Association of Body Mass Index With Coronary Artery Calcium and Subsequent Cardiovascular Mortality: The Coronary Artery Calcium Consortium. (July 2020) - Jensen, Joseph C.; Dardari, Zeina A.; Blaha, Michael J.; White, Susan; Shaw, Leslee J.; Rumberger, John; Rozanski, Alan; Berman, Daniel S.; Budoff, Matthew J.; Nasir, Khurram; Miedema, Michael D.
Abstract : Background: Obesity is associated with higher risk for coronary artery calcium (CAC), but the relationship between body mass index (BMI) and mortality is complex and frequently paradoxical. Methods: We analyzed BMI, CAC, and subsequent mortality using data from the CAC Consortium, a multi-centered cohort of individuals free of established cardiovascular disease (CVD) who underwent CAC testing. Mortality was assessed through linkage to the Social Security Death Index and cause of death from the National Death Index. Multivariable logistic regression was used to determine odds ratios for the association of clinically relevant BMI categories and prevalent CAC. Cox proportional hazards regression modeling was used to determine hazard ratios for coronary heart disease, CVD, and all-cause mortality according to categories of BMI and CAC. Results: Our sample included 36 509 individuals, mean age 54.1 (10.3) years, 34.4% female, median BMI 26.6 (interquartile range, 24.1–30.1), 46.6% had zero CAC, and 10.5% had CAC ≥400. Compared with individuals with normal BMI, the multivariable adjusted odds of CAC >0 were increased in those overweight (odds ratio, 1.13 [95% CI, 1.1–1.2]) and obese (odds ratio, 1.5 [95% CI, 1.4–1.6]). Over a median follow-up of 11.4 years, there were 1550 deaths (4.3%). Compared with normal BMI, obese individuals had a higher risk of coronary heart disease, CVD, and all-cause mortality while overweight individuals, despite a higher odds of CAC, showed no significant increase in mortality. In a sex-stratified analysis, the increase in coronary heart disease, CVD, and all-cause mortality in obese individuals appeared largely limited to men, and there was a lower risk of all-cause mortality in overweight women (hazard ratio, 0.79 [95% CI, 0.63–0.98]). Conclusions: In a large sample undergoing CAC scoring, obesity was associated with a higher risk of CAC and subsequent coronary heart disease, CVD, and all-cause mortality. However, overweight individuals did not have a higher risk of mortality despite a higher risk for CAC.